2010
DOI: 10.1097/qai.0b013e3181b56404
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Retention Among African American and Latino Adolescent HIV-Positive Men: Results From the Outreach, Care, and Prevention to Engage HIV-Seropositive Young MSM of Color Special Project of National Significance Initiative

Abstract: Special Projects of National Significance programs were able to achieve a high level of retention over time, and individual and program characteristics were associated with retention. Latino YMSM, those not receiving services, and those not perceiving respect at the clinic were at increased risk of falling out of care. Retention is essential to providing HIV+ adolescents with treatment, including reducing antiretroviral resistance development. Innovative programs that address the needs of the YMSM of color pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 27 publications
3
89
1
Order By: Relevance
“…Though retention and suppression are often treated separately in the literature, 11,[16][17][18][19][20]35,36 this study examined both measures by focusing on an impoverished, vulnerable prospective cohort of WOC. For these women, our findings suggest that retention and viral suppression were influenced by different factors, and that interventions seeking to improve retention may require program components and strategies that differ from interventions aiming to improve viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Though retention and suppression are often treated separately in the literature, 11,[16][17][18][19][20]35,36 this study examined both measures by focusing on an impoverished, vulnerable prospective cohort of WOC. For these women, our findings suggest that retention and viral suppression were influenced by different factors, and that interventions seeking to improve retention may require program components and strategies that differ from interventions aiming to improve viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers reported that high rates of depressive symptomology was common among this population Magnus, Jones, et al, 2010;. Although a modest number of articles addressed depressive symptomology, only four articles addressed the issue of suicide, and two articles addressed the issues of bullying/harassment and abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, researchers reported that Black YGBMSM were more likely to receive prevention and counseling services from their providers as well as report greater use of and satisfaction with their health care providers (Behel et al, 2008). Other studies, however, reported that some Black YGBMSM experience difficulties in trusting providers and perceive a lack of respect on the part of providers (Magnus, Jones, et al, 2010;Mashburn et al, 2004). Given the recent changes surrounding accessibility to health insurance through the Affordable Care Act, and the subsequent opportunities to enhance public health prevention efforts, these factors may be of growing significance to both researchers and practitioners (Koh & Sebelius, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…23 Each of the eight sites operated independently, using different strategies to conduct outreach, HIV testing and linkage to care for HIV-positive YMSM of color. The eight sites used a common data collection tool and common eligibility requirements to allow for cross-site comparisons.…”
Section: Data Collectionmentioning
confidence: 99%